THU0488 New Zoledronate Database Significantly Improves Pre-Assessments and Waiting Times To Repeat Infusions – Results from A Quality Improvement Project. (15th July 2016) - Vasireddy, S.; Allman, C.; Farrant, J.; Ammori, M.; Khan, N.; Bromilow, L.
Abstract : Background: IV Zoledronate is used to treat osteoporosis patients who failed an oral bisphosphonate. Checking adjusted calcium (Ca), serum creatinine (Cr), estimated GFR, vitamin D and PTH before infusion can help optimise treatment outcomes. Previous audit demonstrated that our department was failing to reach 100% pre-infusion assessment (92% had Ca, Cr and eGFR; 85% Vitamin D and 74% PTH). Our previous zoledronate data was on an MS Excel spreadsheet with no audit or next due date functionality (service target: to deliver annual infusions within a month of due date). A database with these functionalities is not commercially available. Objectives: We aimed to develop such a database, and demonstrate its Quality Improvement/audit functionality through analysis of waiting times to repeat infusions, and re-audit of pre-infusion assessments. Methods: The new database was created in MS Access 2010 and introduced in Oct 14. Fields included Ca, Cr, eGFR, vit D and PTH. Functions were created to automatically generate next due date, and to view a list of patients in order of next due date. Waiting times were compared for repeat infusions before and after database was introduced. A proportion of all consecutive patients receiving infusions (first and repeat) since database started were selected for analysis of pre-infusion assessment. Biochemistry laboratory ranges were used for interpreting Ca (2.20–2.60mmol/l) and PTH (1.1–7.4 pmol/L); and to stratify total 25 hydroxy vit D (nmol/L; as used in previous audit: <25 = deficiency; 26–50 = insufficiency; 51–75 = adequate; 76–250 = optimal). EGFR (ml/min) was stratified according to the Chronic Kidney Disease stage (>90 = 1; 60–89=2; 30–59=3; 15–29=4; <15=5). Data were transferred to MS Excel 2010 for processing and descriptive statistics. Results: 68 consecutive patients before Oct 14 and 65 consecutive patients from Oct 14 to Jan 16 who received repeat infusions were eligible for comparison. Improvements included more receiving infusion within target date (23.5% v 35.4%); and reduced waiting time (days) beyond target (mean 62.6 v 38.2; median 31 v 18). 35 consecutive patients who received zoledronate between Oct 14 and Feb 15 were identified for analysis of pre-assessments (27 women, 8 men; mean age 76.6±9.4yrs, range 52–91yrs). 35 (100%) had Cr and eGFR, 34 (97%) had Ca and vit D, and 25 (71%) had PTH. Mean Ca was 2.34±0.1mmol/l (range 2.2–2.59); Cr 88.5±17.4umol/l (59–122); eGFR 67.1±13.5ml/min (41–90); Vit D 77.2±30.5 (32–203) and PTH 5.1±2.3pmol/L (2–9.9). Vit D was deficient in 0, insufficient in 3 (8.8%), adequate in 15 (44.1%) and optimal in 14 (41.2%) (1 insufficient sample). eGFR was normal in 8 (22.8%); CKD2 in 19 (54.3%); CKD3 in 8 (22.9%) and none in CKD4 or 5. Conclusions: Introduction of the purpose-built new database has achieved significant reduction in waiting times, and improvements in pre-infusion assessment (100% Cr and eGFR, and 97% Ca and Vit D compared to previous audit's 92% for Cr, eGFR and Ca and 85% for Vit D). The re-audit also confirmed overall improvement in Vit D levels (85% v 46% adequate or optimal), and 100% safety with respect to acceptable Ca and eGFR pre-infusion. We expect further improvements in waiting times for repeat infusions on a later re-audit when all patients entered on the database for first infusion complete a repeat infusion. Disclosure of Interest: None declared